Quantum-dot-sensitized solar cells - Pan, Lei (2013)
Poor absorption of low-energy photons by available dyes are one of major factors limiting further improvement in the photo-conversion efficiencies achievable using nanocrystalline Dye-sensitized solar cells (DSSCs). Quantum dots (QDs) provide the ability to match the solar spectrum better and can generate multiple electron-hole pairs per photon, which could improve the efficiency of the device.[1] In this project, quantum-dot-sensitized solar cell (QDSC) will be fabricated. [1st Award]